2015
DOI: 10.1038/onc.2015.369
|View full text |Cite
|
Sign up to set email alerts
|

Expression and therapeutic targeting of dopamine receptor-1 (D1R) in breast cancer

Abstract: Patients with advanced breast cancer often fail to respond to treatment, creating a need to develop novel biomarkers and effective therapeutics. Dopamine (DA) is a catecholamine which binds to five G-protein-coupled receptors. We discovered expression of DA type-1 receptors (D1R) in breast cancer, thereby identifying these receptors as novel therapeutic targets in this disease. Strong to moderate immunoreactive D1R expression was found in 30% of 751 primary breast carcinomas, and was associated with larger tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 47 publications
6
86
1
2
Order By: Relevance
“…It is reported that a partial agonist of DRD1-like receptors, Fenoldopam, causes tumor shrinkage in the mouse xenograft model through the cGMP/protein kinase G (PKG) pathway27. We also observed reduction in cell proliferation in 4T1.2 cells (Suppl.…”
Section: Discussionmentioning
confidence: 56%
“…It is reported that a partial agonist of DRD1-like receptors, Fenoldopam, causes tumor shrinkage in the mouse xenograft model through the cGMP/protein kinase G (PKG) pathway27. We also observed reduction in cell proliferation in 4T1.2 cells (Suppl.…”
Section: Discussionmentioning
confidence: 56%
“…Expression of DA D 1 receptors was found in 30% of patients with primary breast carcinomas and was associated with larger tumors, higher tumor grades, node metastasis, and shorter patient survival. However, in vitro activation of the D 1 ‐receptor/cGMP/protein kinase G pathway suppressed cell viability, inhibited invasion and induced apoptosis (70). It seems counterintuitive that increased D 1 ‐receptor expression correlates positively with advanced disease, whereas D 1 ‐receptor activation results in apoptosis.…”
Section: Interaction Between Da and Angiogenesismentioning
confidence: 99%
“…Borcherding et al (70) hypothesized several mechanisms to explain the counterintuitive positive correlation between DA signaling and malignant behavior observed in vitro in human breast cancer cells, such as changes in the role of the D 1 receptor and the cGMP apoptotic pathway during tumor progression and metastatic stages of the disease. Mechanisms similar to these may also be applicable in malignant PCC and PGL.…”
Section: Da Synthesis and Hypoxia Are Linked In Pcc And Pglmentioning
confidence: 99%
“…Dopamine receptors (DRD1-5) mainly reside in the human brain, which play important roles in cancer tumorigenesis and progression [5][6][7][8][9]. DRD2 agonists inhibit the growth of lung cancer cells including NSCLC and small cell lung cancer [6,10,11].…”
Section: Introductionmentioning
confidence: 99%